Investigating the dehydrogenation pathway for lithium borohydride / hydroxide system - Munshi, Sweta (2024)
Developing a cost effective and energy dense hydrogen storage system with a moder-ate operating condition is one the key challenges in hydrogen economy. Lithium boro-hydride (LiBH4) has gained much interest as a hydrogen storage material due to its high gravimetric and volumetric hydrogen density of 18.5 wt.% and 121 kg/m3. How-ever, key drawbacks include high stability, slow kinetics, and a high dehydrogenation temperature (400–600 ºC). In order to decrease the decomposition temperature and enhance the kinetics of LiBH4, a technique called thermodynamic tuning can be used. Thermodynamic tuning involves creating new, more favourable reaction pathways by adding a secondary material.